1997
DOI: 10.1073/pnas.94.26.14285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional expression of a human cDNA encoding translation initiation factor 6

Abstract: Eukaryotic translation initiation factor 6 (eIF6) binds to the 60S ribosomal subunit and prevents its association with the 40S ribosomal subunit. In this paper, we devised a procedure for purifying eIF6 from rabbit reticulocyte lysates and immunochemically characterized the protein by using antibodies isolated from egg yolks of laying hens immunized with rabbit eIF6. By using these monospecific antibodies, a 1.096-kb human cDNA that encodes an eIF6 of 245 amino acids (calculated M r 26,558) has been cloned and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 25 publications
1
61
0
Order By: Relevance
“…Under similar assay conditions, eIF6, which binds to 60 S ribosomal subunits, prevents the association of 40 S and 60 S ribosomal subunits (data not shown here; see Refs. [21][22][23]). These results demonstrate that in contrast to other reports (18 -20), eIF1A and eIF3 by themselves do not have ribosomal subunit antiassociation activity in the absence of Met-tRNA f and other initiation components.…”
Section: Formation Of the 40 S Preinitiation Complexmentioning
confidence: 99%
“…Under similar assay conditions, eIF6, which binds to 60 S ribosomal subunits, prevents the association of 40 S and 60 S ribosomal subunits (data not shown here; see Refs. [21][22][23]). These results demonstrate that in contrast to other reports (18 -20), eIF1A and eIF3 by themselves do not have ribosomal subunit antiassociation activity in the absence of Met-tRNA f and other initiation components.…”
Section: Formation Of the 40 S Preinitiation Complexmentioning
confidence: 99%
“…One potential marker is an intriguing protein, p27 BBP , that has already been reported to be highly increased in colorectal carcinoma and related to its progression. 1 Previous research has established that this protein, originally identified as an interactor of the large cytodomain of integrin h4 2 and as a putative eukaryotic initiation factor (eIF6), 3 is an essential regulator of the 60S ribosome assembly. 4,5 Its evolutionary conservation (more than 85% identity between human and yeast) suggests that p27 BBP controls a crucial event within the protein synthesis pathway that has been maintained throughout eukaryotic evolution.…”
mentioning
confidence: 99%
“…However, p27 BBP has also been found in a cytoplasmic soluble form and in a cytoskeletonassociated insoluble form. 2,3 These multiple locations suggest that p27 BBP may play different roles in different cellular structures but also suggest that a potential unifying role as a local controller of ribosome assembly may be served by p27 BBP wherever protein synthesis occurs.…”
mentioning
confidence: 99%
“…eIF-6 has been purified from a variety of eukaryotic cells, including wheat germ, calf liver, and rabbit reticulocytes (12)(13)(14)(15). In addition, we and others have cloned the murine and human genes that encode this protein (10,16,17). eIF-6 is highly conserved among eukaryotic cells, and human and murine eIF-6 share 97.5% amino acid sequence homology.…”
mentioning
confidence: 99%
“…In all species, eIF-6 is a monomer with a molecular mass of appoximately 26 kDa (12)(13)(14)(15). eIF-6 has been reported to bind to the 60S ribosomal subunit and prevent its association with the 40S ribosomal subunit in several different eukaryotic organisms (13)(14)(15)(16)18). Several lines of evidence indicate that eIF-6 is important for ribosome biogenesis by regulating cellular levels of free 60S subunit (11,19,20).…”
mentioning
confidence: 99%